FEATURES OF WORK ON THE PROJECT "THE TOURISTIC AND LANGUAGE CAMP "SUCCESS" FOR STUDENTS OF THE SPECIALTY "TOURISM" - Kifik, N.Yu.; Ogienko, N.A.; Malshakova, V.V.; Shkvarenko, N.S. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
The article deals with the implementation of the trilingual education program by organizing a summer language camp. The characteristics of the organization of the given camp, features of its functioning are given. It is noted what skills and skills will be formed in the participants of this camp both in the language sphere and in the tourist sphere.
Keywords: trilingual education; language camp; tourist camp; language skills; language competence; tourist skills; self-esteem; motivation